OPEC study: An international multicenter study of ovarian preservation in endometrial cancers. Issue 2 (14th April 2022) - Akgor, Utku; Ayhan, Ali; Shushkevich, Alexander; Ozdal, Bulent; Angelou, Kyveli; Akbayır, Ozgur; Kaidarova, Dilyara; Ulrikh, Elena; Stepanyan, Artem; Ortac, Fırat; Aliyev, Shamistan; Ozgul, Nejat; et al.
Abstract: Objective: To evaluate the feasibility and oncological safety of ovarian preservation in early stage endometrial adenocarcinoma (EC) patients aged 40 and below. Methods: A total of 11 institutions from eight countries participated in the study. 169 of 5898 patients aged ≤40 years were eligible for the study. Patients with EC treated between March 2007 and January 2019 were retrospectively assessed. Results: The median duration of follow‐up after EC diagnosis was 59 months (4–187). Among 169 participants, ovarian preservation surgery (OPS) was performed in 54 (31.9%), and BSO was performed in 115 (68.1%) patients. Although patients younger than 30 years of age were more likely to have OPS than patients aged 30 to 40 years (20.4% vs. 9.6%, P =  0.021), there was no significant difference by the mean age. There were no other relevant baseline differences between OPS and BSO groups. The Kaplan–Meier analysis revealed no difference in either the overall survival ( P =  0.955) or recurrence‐free survival ( P =  0.068) among patients who underwent OPS, and BSO. Conclusion: OPS appears to be safe without having any adverse impact on survival in women aged ≤40 years with FIGO Stage I EC.